Comparison of ExoMol simulated spectra for H2O to high-temperature low-pressure gas cell measurements at 1723K in the 7321–7598 cm−1 range. (September 2020) - Melin, S.T.; Sanders, S.T.; Nasir, E.F.
Highlights: Accuracy of ExoMol H2O absorption simulation comparison with measurement at 1723 K. Over 675 absorption features compared across the 7300 – 7600 cm -1 range. ExoMol simulation showed measurable improvement over BT2 in range studied. ExoMol promising for broad-band, high-temp H2 O absorption spectroscopy applications. Abstract: Sensors based on absorption spectroscopy rely on accurate simulations to obtain quantitative data. The simulations, in turn, depend on accurate line lists. To test the quality of the ExoMol line list, a comparison of a simulation based on the line list to a measured H2 O absorption spectrum recorded in a heated static cell was performed. The spectrum spanned the 7326 – 7598 cm −1 range and was measured at a temperature of 1723 K. A root mean square (RMS) error of 0.00049 [-] was calculated for the ExoMol comparison, roughly six times better than the same comparison based on the BT2 database. A detailed comparison was performed on approximately 675 of the strongest peaks in the measured spectrum. The comparison identified approximately 9% of the simulated features containing residual errors >10% of the measured absorption. Of these absorption features, 18 were categorized as missing or additional features in the simulation while 29 were identified as having a mismatch in strength or position between simulation and measurement. Based on the results, it is believed that remaining errors in the ExoMol line list will not significantly compromise absorption thermometry techniques which incorporate a broad spectral range in typical combustion applications.